Promoting quality improvement in French healthcare organisations: design and impact of a compendium of models and tools. Issue 5 (7th October 2003) - Erbault, M; Glikman, J; Ravineau, M-J; Lajzerowicz, N; Terra, J-L
Abstract : Relevant and user friendly information should be provided to professionals who wish to promote quality improvement in healthcare organisations (HCOs). In response to requests from French HCOs, we designed a compendium of methods and tools for use in quality improvement. Its contents were based on a critical review of the literature, face-to-face interviews with three industrial/business experts in quality, the views of 13 healthcare professionals knowledgeable in quality issues, and comments from over 40 potential users of the compendium. Overall, 14 methods and 20 tools relevant and applicable to the healthcare sector were identified. They were classified according to their main thrust, explained in detail, illustrated with specific cases from the literature or from personal experience, and published as a loose leaf compendium. The compendium was posted on the worldwide web and presented to healthcare managers in September 2000. It has become one of the most popular ANAES publications (approximately 5400 downloads over the first 6 months), partly because all French HCOs are legally bound to undergo accreditation which has been set up and is being implemented by ANAES.